Avaliação da influência da PGF2α e do GnRH em um protocolo curto de IATF em novilhas Nelore - Silvestri, Mayara (2020)
This study aimed to evaluate the use of PGF2α in D0 and / or GnRH at the time of AI and in pregnancy by AI (P / AI) in heifers submitted to an E2-based protocol and P4 device for seven days. 1024 Nellore heifers were used (~ 2 years), randomly divided. Group P0G0 received estradiol benzoate and placed a new intravaginal device of P4 for seven days and PGF2α, eCG and estradiol cypionate. In D9, IAFT is made. Groups P1G0 and P0G1 differed by treatments with PGF2α in D0 and GnRH in AI, respectively. In the P1G1 group, heifers were treated with PGF2α in D0 and GnRH in D9. Estrus expression, presence of CL in D0 and pregnancy diagnosis in D40 were evaluated. The statistical analysis was performed by GLIMMIX with SAS (LSM ± SEM; P≤0.05). There was no difference in P / AI between treatments, but there was a tendency for the GnRH effect, with no effect for PGF2α. The presence of CL at the beginning of the protocol on the expression of estrus showed interaction, not differing between groups. In addition, there was no interaction between GnRH in AI and the expression of estrus in P / AI. However, GnRH increased the fertility of oestrous heifers, however, it did not alter the fertility of non-estrous heifers. Treatment with PGF2α at D0 had little or no effect on P / AI, but GnRH at the time of AI appears to have improved fertility.